Al-quwwah: The Core of Leadership in Islam - Sofia Nabila Binti Alimin, Nur; Rahmah Binti Awang, Siti; Bin Ahmad, Tahir; Bin Safar, Jima’ain; Bin Mohd Nain, Shukri (International Journal of Engineering and Technology, 2018)
This article discusses the concept of Al-Quwwah as the core of leadership in Islam, as well as the crucial elements in Al-Quwwah in instilling this concept in the present leadership. The elements of Al-Quwwah are strength of mind (â€˜aqliyyah), strength of soul (nafsiyyah), knowledge and physical strength.Â